Leptin-a mediates transcription of genes that participate in central endocrine and phosphatidylinositol signaling pathways in 72-hour embryonic zebrafish (Danio rerio) - Tuttle,Matthew; Dalman,Mark R.; Liu,Qin; Londraville,Richard L. (PeerJ, 2019)
We analyzed microarray expression data to highlight biological pathways that respond to embryonic zebrafish Leptin-a (lepa) signaling. Microarray expression measures for 26,046 genes were evaluated from lepa morpholino oligonucleotide “knockdown”, recombinant Leptin-a “rescue”, and uninjected control zebrafish at 72-hours post fertilization. In addition to KEGG pathway enrichment for phosphatidylinositol signaling and neuroactive ligand-receptor interactions, Gene Ontology (GO) data from lepa rescue zebrafish include JAK/STAT cascade, sensory perception, nervous system processes, and synaptic signaling. In the zebrafish lepa rescue treatment, we found changes in the expression of homologous genes that align with mammalian leptin signaling cascades including AMPK (prkaa2), ACC (acacb), Ca2+/calmodulin-dependent kinase (camkk2), PI3K (pik3r1), Ser/Thr protein kinase B (akt3), neuropeptides (agrp2, cart1), mitogen-activated protein kinase (MAPK), and insulin receptor substrate (LOC794738, LOC100537326). Notch signaling pathway and ribosome biogenesis genes respond to knockdown of Leptin-a. Differentially expressed transcription factors in lepa knockdown zebrafish regulate neurogenesis, neural differentiation, and cell fate commitment. This study presents a role for zebrafish Leptin-a in influencing expression of genes that mediate phosphatidylinositol and central endocrine signaling.
Keywords: Leptin; Expression; Embryo; Gene; Transcriptome; Zebrafish; Signaling; Regulation; Microarray; Teleost